A Case of Aggressive Multiple Myeloma with Extramedullary Involvement of the Female Reproductive System, Thyroid and Breasts. (31st July 2019) - Khan, Abdul Moiz; Azar, Ibrahim; Najjar, Saleh; Bevington, Travis; Mehdi, Syed
Abstract : Extramedullary disease at the time of diagnosis of multiple myeloma is a rare finding that portends poor prognosis and necessitates aggressive treatment strategies. We present a case of multiple myeloma with extramedullary plasmacytomas of the female reproductive system, thyroid and breasts. The patient was treated with lenalidomide, bortezomib, cyclophosphamide, and dexamethasone. Follow-up PET-CT scans confirmed clinical complete response, and the patient underwent autologous stem cell transplantation. The patient will be continued on lenalidomide and bortezomib maintenance therapy. To the best of our knowledge, simultaneous involvement of these sites has never been reported. The case highlights that there are no established guidelines on the treatment of multiple myeloma with extramedullary disease leading to great variability based on clinician preference. We will also discuss the treatment options and prognosis of multiple myeloma with extramedullary disease.